L'aspiration en basque: phonématique et analogie - Gonzalez-Eppherre, Jean-Philippe; Oihartzabal, Beñat (Anuario del Seminario de Filología Vasca "Julio de Urquijo.", 2025)
Cette étude se divise en deux parties: dans un premier temps est examiné le phénomène de l’aspiration basque dans ses occurrences et extensions diachroniques et diatopiques, sous les aspects distincts de l’emprunt, de l’imitation analogique et du renforcement accentuel, ainsi que sous celui de son fondement étymologique interne; dans un deuxième temps, sur la base de cet examen, une hypothèse est formulée sur l’origine phonétique de l’aspiration en basque comme résultant de l’affaiblissement articulatoire d’un ancien phonème fricatif uvulaire aujourd’hui disparu (voir aussi, dans le même sens, mais de manière indépendante, Manterola & Hualde 2021). La conclusion générale de l’étude tend par suite à établir que l’aspiration basque actuelle résulte, en premier lieu, de l’évolution d’un phonème antique, puis, en second lieu, d’un phénomène phonotactique, géographiquement délimité, d’extension purement analogique du phonème. This study is divided into two parts. First, it examines the phenomenon of Basque aspiration in its diachronic and diatopic occurrences and extensions, considering its various manifestations as borrowing, analogical imitation, and prosodic reinforcement, as well as its etymological basis. Second, building upon this examination, a hypothesis is proposed regarding the phonetic origin of aspiration in Basque, suggesting that it results from the articulatory weakening of a former uvular fricative phoneme that has since disappeared (see also Manterola & Hualde 2021, who independently arrive at a similar conclusion). The general conclusion of the study, therefore, is that modern Basque aspiration originates, first, from the evolution of an ancient phoneme, and second, from a geographically circumscribed phonotactic phenomenon involving the purely analogical extension of that phoneme. This study is divided into two parts. First, it examines the phenomenon of Basque aspiration in its diachronic and diatopic occurrences and extensions, considering its various manifestations as borrowing, analogical imitation, and prosodic reinforcement, as well as its etymological basis. Second, building upon this examination, a hypothesis is proposed regarding the phonetic origin of aspiration in Basque, suggesting that it results from the articulatory weakening of a former uvular fricative phoneme that has since disappeared (see also Manterola & Hualde 2021, who independently arrive at a similar conclusion). The general conclusion of the study, therefore, is that modern Basque aspiration originates, first, from the evolution of an ancient phoneme, and second, from a geographically circumscribed phonotactic phenomenon involving the purely analogical extension of that phoneme. This study is divided into two parts. First, it examines the phenomenon of Basque aspiration in its diachronic and diatopic occurrences and extensions, considering its various manifestations as borrowing, analogical imitation, and prosodic reinforcement, as well as its etymological basis. Second, building upon this examination, a hypothesis is proposed regarding the phonetic origin of aspiration in Basque, suggesting that it results from the articulatory weakening of a former uvular fricative phoneme that has since disappeared (see also Manterola & Hualde 2021, who independently arrive at a similar conclusion). The general conclusion of the study, therefore, is that modern Basque aspiration originates, first, from the evolution of an ancient phoneme, and second, from a geographically circumscribed phonotactic phenomenon involving the purely analogical extension of that phoneme.